Neuroimaging Characteristics of Nasopharyngeal Carcinoma in Children. Issue 1 (30th August 2020) - Orman, Gunes; Tran, Brandon H.; Desai, Nilesh; Meoded, Avner; Kralik, Stephen; Smith, Valeria; Hicks, John; Kirsch, Claudia; Huisman, Thierry A. G. M.
ABSTRACT: BACKGROUND AND PURPOSE: Pediatric nasopharyngeal carcinoma (NPC) is a rare epithelial origin tumor associated with undifferentiated histology, Epstein–Barr virus (EBV) infection, and genetic risk factors. Childhood NPC is usually clinically silent, often presenting with advanced locoregional compromise, including skull base invasion and cervical lymphadenopathy, and has a better prognosis than adult NPC. This article describes computed tomography (CT) and magnetic resonance imaging (MRI) features in a cohort of 28 pediatric NPC patients. METHODS: A retrospective review was performed among children with histopathology proven NPC diagnoses between 1996 and 2019 for this study. The electronic medical records were reviewed to determine demographics, EBV serology, and World Health Organization (WHO) type. Nasopharyngeal CT and/or MRI at presentation for tumor spread as well as density and/or intensity, lymphadenopathy, postcontrast enhancement and diffusion characteristics before treatment were evaluated. RESULTS: Twenty‐eight patients (21 males, 7 females) were included. The mean patient age at diagnosis was 13.3 (range 7 to 17) years. EBV was positive in 71.4% of patients. The majority of patients (78.6%) had a WHO type III tumor, unilateral fossa of Rosenmuller involvement (71.4%). Neuroimaging features were CT isodensity, T1‐isointensity, T2‐hyperintensity, and heterogeneous postcontrast enhancement for all patients (100%) and restricted diffusion (90%). CONCLUSIONS: Although uncommon in pediatric patients, NPC should be in the differential diagnosis of adolescents presenting with a nasopharyngeal mass. Recognizing key imaging characteristics is helpful in the diagnosis of NPC.